Proceedings of the Ninth International Conference on Deep and High Stress Mining 2019
DOI: 10.36487/acg_rep/1952_29_morkel
|View full text |Cite
|
Sign up to set email alerts
|

The validity of Es/Ep as a source parameter in mining seismology

Abstract: It is generally accepted that the ratio of energy associated with the S-wave (Es) and P-wave (Ep) is dependent on the focal mechanism (Mendecki 2013). In the mining industry, the ratio of S-wave energy to P-wave energy is regarded as an important indicator of the type of focal mechanism, with the ratio being lower for explosive sources and higher for fault slip (Cai et al 1998, Mendecki, 2013). In pure shear, the Es is considerably larger than Ep (Es/Ep > 20). For the tensile model, Sato (1978) has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The reliability of E S / E P ratios as an indicator of source mechanism has recently been questioned by Morkel et al . [83]. Shearing sources are expected to have f oP / f oS > 1 (table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reliability of E S / E P ratios as an indicator of source mechanism has recently been questioned by Morkel et al . [83]. Shearing sources are expected to have f oP / f oS > 1 (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of E S / E P ratios as an indicator of source mechanism has recently been questioned by Morkel et al . [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated source mechanism using the Es/Ep ratio (Morkel et al 2019) showed that 70 out of 83 large events and seven out of eight very large events had a non-shear source mechanism using Es/Ep = 10 as a boundary between non-shear and shear events. Figures 8 and 9 show the locations of the non-shear and shear large events within 0.5 magnitude intervals.…”
Section: Dynamic Source Parametersmentioning
confidence: 99%
“…(1998), Kwiatek and Ben‐Zion (2013), Morkel et al. (2019), Liu et al. (2020), Rebuli and Kohler (2014) and Sweby et al.…”
Section: Introductionmentioning
confidence: 99%